Waste Analysis of Sugar Production Process Using Lean Six Sigma Method - Fitriani, Ella; Rochmoeljati, Rr. (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
The Sugar factory is a manufacturing company that produces sugar. The product produced is Super High Sugar (SHS) white crystal sugar. In the production process, there are still several problems that occur in the form of waste including product defects, excess storage, delay, and other problems that cause a very long lead time of 1410 minutes or equivalent to 23.5 hours. This study aims to determine the type of waste that occurs through the calculation of Defect Per Million Opportunity (DPMO) and sigma level and provide suggestions for improvement. The results showed that the biggest waste occurred in defects, waiting, and unnecessary inventory with a waste weight of 3.0; 2.9; and 2.5, respectively. The DPMO value is 55188 and the sigma level is 3.096. The Failure Mode Effect and Analysis (FMEA) method and Risk Priority Number (RPN) value were applied to analyze the causes of waste and provide suggestions for improvement. Recommendations for the company are to carry out routine machine maintenance and control raw materials before entering the production process. This research contributes other solutions to help management overcome waste during the production process.